2008
DOI: 10.1182/blood-2007-05-091504
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide sensitizes AML cells to TRAIL-induced apoptosis via decrease of XIAP and p53-mediated increase of DR5

Abstract: Acute myeloid leukemia (AML) cells are relatively resistant to tumor necrosis factor ␣-related apoptosis-inducing ligand (TRAIL). We previously reported that triptolide, a potent anticancer agent from a Chinese herb, decreases XIAP in leukemic cells. We evaluated the combination of triptolide and TRAIL and found synergistic promotion of apoptosis in AML cells. XIAP-overexpressing U937 cells (U937XIAP) were more resistant to TRAIL than U937neo cells, and inhibition of XIAP with the small-molecule inhibitor 1396… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 56 publications
(60 reference statements)
3
97
1
Order By: Relevance
“…33,46 Our data provide evidence that such therapeutic strategies can be improved by incorporation of agents such as nutlin-3a, in agreement with others. 47,48 Recent studies have shown that nutlin-3a, at very high concentrations, usually 420-30 mM, can inhibit the growth of cancer cells with deleted p53, or harbouring a nonfunctional, mt p53 gene, although the exact mechanism is incompletely understood. 35,36 It seems, depending on the in vitro system, that activation of other partners of Mdm2, including p73 or E2F1, may be involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…33,46 Our data provide evidence that such therapeutic strategies can be improved by incorporation of agents such as nutlin-3a, in agreement with others. 47,48 Recent studies have shown that nutlin-3a, at very high concentrations, usually 420-30 mM, can inhibit the growth of cancer cells with deleted p53, or harbouring a nonfunctional, mt p53 gene, although the exact mechanism is incompletely understood. 35,36 It seems, depending on the in vitro system, that activation of other partners of Mdm2, including p73 or E2F1, may be involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,16,[21][22][23] Importantly, treatment with Ara-C alone significantly increased the transcription of BCL2 and XIAP (P ¼ 0.0002 and P ¼ 0.0028, respectively). Both of these genes have been implicated in drug resistance mechanisms in AML [24][25][26][27] and so their transcriptional activation may limit the apoptotic response to Ara-C. Remarkably, the combination of SNS-032 and Ara-C resulted in decreased MCL1 expression Figure 5 The existence of synergy between SNS-032 and Ara-C was determined using a ratio of 1 SNS-032 to 1.9 Ara-C and treating 25 primary AML samples to these two agents separately and in combination for 48 h. The cyclin-dependent kinase inhibitor SNS-032 has single agent activity in AML E Walsby et al (P ¼ 0.021) and decreased expression of XIAP (Po0.0001) and BCL2 (P ¼ 0.0002), providing a rationale for at least one mechanism for the synergy seen with these agents.…”
Section: Molecular Determination Of Mechanisms Of Synergymentioning
confidence: 99%
“…Newly report shown that triptolide have the potential to suppress the proliferation of human tumors in vitro (Zhu et al, 2009;Borja-Cacho et al, 2010;Clawson et al, 2010;Zhao et al, 2010;Lu et al, 2011). It is worth noting that triptolide possess side effects in both immunosuppressive and antifertility activities (Carter et al, 2008;Westfall et al, 2008;Yang et al, 2008;Chen et al, 2009). In this, the role of triptolide in cancer treatment needs to be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…Another widely used drug, triptolide, the major composition extracted from the Chinese herb Tripteryglum wilfordii Hook.f, has now been shown that it can inhibit tumor growth (Clawson et al, 2010;Zhao et al, 2010;Lu et al, 2011;Li et al, 2012;Zhu et al, 2012;Huang et al, 2013;Tan et al, 2013). However, triptolide still have side effects such as immunosuppressive and antifertility (Carter et al, 2008;Westfall et al, 2008;Yang et al, 2008;Chen et al, 2009;Zhu et al, 2009;Borja-Cacho et al, 2010).…”
Section: Enhanced Anti-tumor Efficacy Of Aspirin Combined With Triptomentioning
confidence: 99%